Reliability and validity DASS 21: Malay students / Kartini Kasim...[et al.] - Kasim, Kartini; Ahmad, Anis Mardiana; Ismail, Nur Sa’aidah; Shamsuddin, Norin Rahayu; Wan Salleh, Wan Zulkipli; Kamaruddin, Kardina; Mohamed Ramli, Norazan (2015)
A study was conducted to examine the reliability and validity of Depression Anxiety Stress Scale -21 (DASS 21) among undergraduate students. A total of 79 Malay students were involved in this study. Our result indicates the internal consistency of 21-item versions of the questionnaire are typically high (cronbach alpha = 0.881). The factor loading analysis also shown a good factor loading for most items (ranging from 0.3 to 0.75) which explain the theoretical construct of 21 items are reliable and valid for assessing depression, anxiety and stress in other undergraduates’ students.